Recording the world (Westview, 1994)
This book was designed to supplement and enrich rather than substitute for traditional political geography textbooks and recent theoretical approaches to geopolitics.The focus here is on the application of political geographic ideas, concepts and perspectives to a broad range of current international issues: Global environmental change, territorial nationalism, conflict over natural resources, population growth and migration, international organizations and laws, and new worlds of multinational economics and telecommunications